Optimizing treatment for older adults with depression - Maytinee Srifuengfung; Bethany R. Tellor Pennington; Eric J. Lenze (SAGE Publishing, 2023)
This review presents a comprehensive guide for optimizing medication management in older adults with depression within an outpatient setting. Medication optimization involves tailoring the antidepressant strategy to the individual, ensuring the administration of appropriate medications at optimal dosages. In the case of older adults, this process necessitates not only adjusting or changing antidepressants but also addressing the concurrent use of inappropriate medications, many of which have cognitive side effects. This review outlines various strategies for medication optimization in late-life depression: (1) Utilizing the full dose range of a medication to maximize therapeutic benefits and strive for remission. (2) Transitioning to alternative classes (such as a serotonin and norepinephrine reuptake inhibitor [SNRI], bupropion, or mirtazapine) when first-line treatment with selective serotonin reuptake inhibitors [SSRIs] proves inadequate. (3) Exploring augmentation strategies like aripiprazole for treatment-resistant depression. (4) Implementing measurement-based care to help adjust treatment. (5) Sustaining an effective antidepressant strategy for at least 1 year following depression remission, with longer durations for recurrent episodes or severe presentations. (6) Safely discontinuing anticholinergic medications and benzodiazepines by employing a tapering method when necessary, coupled with counseling about the benefits of stopping them. Additionally, this article explores favorable medications for depression, as well as alternatives for managing anxiety, insomnia, allergy, overactive bladder, psychosis, and muscle spasm in order to avoid potent anticholinergics and benzodiazepines.